The Friendly beasts : an old English Christmas carol - dePaola, Tomie; De Paola, Tomie (New York : Putnam, 1981)
In this old English Christmas carol the friendly stable beasts tell of the gifts they have given to the newborn Jesus.
Keywords: Christmas; Carols -- England; Christmas music; Folk songs -- England